The effect of drum design on chipper performance. (September 2015) - Spinelli, Raffaele; Cavallo, Eugenio; Eliasson, Lars; Facello, Alessio; Magagnotti, Natascia
Abstract: Chipper design is a main driver of production efficiency within forest fuel supply chains, but little scientific knowledge is available about the performance of different types. Two alternative drum chipper designs were tested on different feedstock types and under different knife wear conditions. The closed drum full-length knife design was more efficient than the open drum staggered-knife design, when negotiating branches, especially when knives were dull. Under these conditions, productivity was higher, fuel use lower and product quality better for the closed drum design. These differences were statistically significant. Therefore, a closed drum design is preferable when branches are the main feedstock, especially if product quality specifications are demanding. In general, the performance of both designs was significantly affected by feedstock type and knife wear. Highlights: We compared a closed-drum chipper with an open-drum chipper. Performance is equivalent when chipping logs. The closed-drum chipper design is more efficient with branches. The difference between the two designs increases with knife wear. In all cases, performance declines rapidly with knife wear.